Une marginalité spatiale comme clé de lecture des territoires - Sylvain Estager (Territoire en Mouvement)
Until the end of the XIX century and the phylloxeric episode, vine was one of the principal resources in Haute-Saône. According to agricultural statistics, since the nineteen seventies this culture has officially disappeared from most of the villages of the department. However, the reality of the fields objects this condition : vine remains an important part of the local landscape. It appears underneath a variety of diverse inscriptions. The vine persists to be employed through diversified practices and related knowledge.For the geographer, this type of subject of investigation is problematic in its global apprehension. Classical sources fail and only the field experience can illustrate the importance of vineyard practices. Vine also requires to be considered in great scale, that of the place. Thus, it is important to find a method and resources to enable the study of the wine in the region and to bring up to date its geographical real meaning.In fact, the vineyard, in its marginal space, is a window through a set of territorial values. It has been part of the daily practices that establish social actors within the regions and participate in their definition. Vine also confirms the importance of the emotional and affective memory in the constructions of the local people identity.Finally, in spite of its supposed marginality, vine is still nowadays a strong issue in the core of regional life.